2009
DOI: 10.1097/id.0b013e3181b8e53c
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Potential of Autogenous Bone Associated with Bone Marrow Osteoblastic Cells in Bony Defects: A Histomorphometric Study

Abstract: Osteoblastic cells associated with autogenous bone accelerated the repair of bone defect, and the action of the osteoblastic cells was more effective until the 10th day and of the autogenous bone after this period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
(20 reference statements)
0
5
0
1
Order By: Relevance
“…Cell-cell interactions between host and donor cells are believed to play an important role in enhancing the healing process after in vivo cell transplantation (Watanabe et al, 1999). In cell therapy for bone defect healing, the delivery of osteogenic cells into the defect area is often considered to be of direct help to the new bone formation (Lacerda et al, 2009). Due to reduced multipotency compared with progenitor cells, osteoblasts may be more committed to form new bone tissue (Leach and Mooney, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cell-cell interactions between host and donor cells are believed to play an important role in enhancing the healing process after in vivo cell transplantation (Watanabe et al, 1999). In cell therapy for bone defect healing, the delivery of osteogenic cells into the defect area is often considered to be of direct help to the new bone formation (Lacerda et al, 2009). Due to reduced multipotency compared with progenitor cells, osteoblasts may be more committed to form new bone tissue (Leach and Mooney, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the method has its limitations, such as the limited availability of tissues, the increased period of time and interventions especially in the case of reconstructions (Misch, 2011). Alternative methods were researched, from which the use of bone marrow aspirate was studied to fill the bone defects to stimulate the healing of fractures and to treat pseudoarthrosis (Lacerda et al, 2009). Using a bone marrow aspirate for the treatment of bone defects on dogs, the improvement of bone formation was obtained (Niemeyer et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, transplant of the autogenous bone block resulted in an intrabony-like space with suffi cient exposure of the bone marrow, which was suitable for fi lling and maintaining particulate bone substitutes and provided better vascularization for bone regeneration. 7 In compromised clinical situations, it is recommended that implants be placed several months after bone grafting because their placement at the time of tissue grafting is appropriate only when optimal positioning can be achieved. 8 A recent systemic review concluded that survival rates of implants placed into augmented areas were comparable with that of implants placed into pristine bone.…”
Section: Discussionmentioning
confidence: 99%